Self-Efficacy and Self-Confidence Strengthening Training for High School Students and Equivalent in Activating Transactional and Interpersonal Communication - Hengki Hengki; Ratna Ratna (NEAR: Jurnal Pengabdian kepada Masyarakat, 2025)
This training aims to enhance self-efficacy and self-confidence among high school students through specialized activities targeting key objectives. These include improving communication skills by teaching effective techniques such as expressing ideas, active listening, and persuasive speaking in both transactional and interpersonal contexts. The program also focuses on building self-efficacy by offering practical scenarios to boost confidence in social interactions. The training incorporates social and interpersonal skill development to strengthen students' ability to navigate daily interactions. Methods are grounded in self-efficacy and confidence theories, emphasizing practical applications through activities like simulations and interactive exercises. A holistic evaluation approach measures self-efficacy and confidence levels before and after the training, alongside the impact on students' transactional and interpersonal communication skills.. The findings reveal significant insights into the importance of strengthening self-efficacy and self-confidence for improving students' communication abilities. Practical implications include aiding in the development of more effective training programs to prepare young people for the demands of the modern workforce and daily life. Additionally, the training highlights the importance of ethical communication norms, fostering healthy interpersonal relationships, and equipping students with strong communication skills to gain a competitive edge in their careers.